New Dynamic Ankle Foot Orthosis (DAFO) / Mohd Nor Azmi Ab Patar … [et al.] - Ab Patar, Mohd Nor Azmi; Mahmud, Jamaluddin; Hamid, Aminuddin; Jamlus, Norman; Komeda, Takashi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
The ankle-foot of human body is a multi-joint structure which provides complex foot motion such as dorsiflexion-plantar flexion, extension, abduction-adduction and inversion-eversion rotation motion. Injury or disease can result in abnormal gait motion of the ankle-foot. Currently, awareness and interest in the Dynamic Ankle Foot Orthosis (DAFO) concept has spread to parents, patients, physical and occupational therapists, orthotists and physicians. The DAFO is a custom moulded product to fit an individual need while providing specific biomechanical help that can be achieved by means of assistance, controlled restraint, or both. A new design of DAFO is needed to resolve the manual and conventional methods that have been using widely in physiotherapy. The design approach of DAFO uses only one degree of freedom (DOF) of foot ankle movement. The rotating movement is controlled by electronics and control devices. The electronic motor gives a suitable torque to help patients to move their foot. The size of the foot base of DAFO is adjustable where the size for adults and children can be customized into two different sizes. The mechanism of DAFO is simple and it is light in weight. This design helps the patients in gaining the ability to walk after experiencing a serious injury. The DAFO has been designed and developed by using the software of Solid works Premium.